Integration of Six Sigma, Fault Tree Analysis, and Design of Experiment in Welding Quality Improvement - Praja Dinata Sembiring; Anizar; Humala Napitupulu (TALENTA Publisher, 2026)
The quality of water wall welding in boiler fabrication remains a critical issue, as a high welding defect rate of 25–30% can lead to leakage, increased repair welding, and reduced reliability of welded joints. This study aims to systematically reduce welding defects and improve the quality of water wall welded joints by integrating Six Sigma, Fault Tree Analysis (FTA), and Taguchi Design of Experiments (DOE). Six Sigma with the DMAIC framework was applied to evaluate process performance and define critical quality characteristics, while FTA was used to identify the dominant root causes of welding defects. The analysis revealed that suboptimal GMAW welding parameters—specifically welding current, root gap, groove angle, and travel speed—were the main contributors to defect formation in water wall welded joints. Taguchi DOE was subsequently employed to determine an optimal and robust combination of welding parameters. The results show that the optimal parameter setting increased the tensile strength of the welded joint to 495.08 MPa and improved the signal-to-noise ratio by 1.36 dB, indicating enhanced welding quality and process stability.The optimized parameters were implemented through an updated Welding Procedure Specification (WPS), enabling the improvement results to be consistently applied in production. This study demonstrates that the integrated Six Sigma–FTA–DOE approach provides an effective and systematic solution for improving water wall welding quality in boiler manufacturing.